Effect of dominant negative MKK expression on pH-induced increases in PEPCK mRNA levels - O'Hayre, Morgan, author; Taylor, Lynn, author; Curthoys, Norman P., author (Colorado State University. Libraries, 2005)
Acid-base homeostasis is essential for survival. When metabolic acidosis is induced by factors such as prolonged starvation, severe shock, high protein diet, or uncontrolled type I diabetes, the kidneys act to compensate for the decreasing pH. Renal catabolism of glutamine, which is sustained through increased expression of phosphoenolpyruvate carboxykinase (PEPCK) and glutaminase (GA), is activated during metabolic acidosis. Mitogen activated protein kinase kinases three and six (MKK3 and MKK6) are thought to play roles in the signal transduction pathway that lead to enhanced PEPCK and glutaminase activity. To examine the potential roles of MKK3 and MKK6, LLC-PK1-FBPase+ cells were stably transfected with dominant negative (dn) forms of either or both kinases. Expression of the transgenes was controlled by a Tetracycline-responsive promoter element (TRE). Doxycycline (dox) is used to inhibit transcription by preventing the tTA transcription factor from binding to the TRE. The absence of dox then enables transcription and turns on expression of the mutated kinase. Western blots were performed on extracts of clonal cell lines to determine the levels of the MKK isoforms as well as the levels of p38 and phosphorylated p38 in LLC-PK1-FBPase+ cells grown in both the absence and presence of dox. Northern blots were also performed to determine the effect of dnMKK expression on levels of PEPCK mRNA. Expression of both dominant negative kinases, but not the expression of either dnMKK3 or dnMKK6 alone, blocked the acid-induced increases in the levels of PEPCK mRNA and the Anisomycin stimulated increases in levels of phosphorylated p38.
Effect of dominant negative forms of MKK3 and MKK6 on pH-responsive induction of PEPCK mRNA
Keywords: Cellular signal transduction; Transcription factors; Messenger RNA